Determinants of Anxiety in the General Latvian Population During the COVID-19 State of Emergency - Jelena Vrublevska; Jelena Vrublevska; Viktorija Perepjolkina; Kristine Martinsone; Jelena Kolesnikova; Ilona Krone; Daria Smirnova; Daria Smirnova; Konstantinos N. Fountoulakis; Elmars Rancans (Frontiers in Public Health, 2022)
BackgroundThe COVID-19 pandemic and its restrictive public health measures have seriously affected mental health of society. Social, psychological, and health-related factors have been linked to anxiety in the general population.AimWe investigate the association of various sociopsychological and health-related determinants of anxiety and identify the predicting factors for anxiety in the general population during the COVID-19 state of emergency from in Latvia.MethodsWe conducted an online survey using a randomized stratified sample of the general adult population in July 2020 for 3 weeks. Anxiety symptoms were measured using the State-Trait Anxiety Inventory (STAI-S). Sociodemographic, health-related, sociopsychological characteristics and suicidality were identified using the structured questionnaire. The statistical analysis included Pearson's chi-square test, post hoc analysis, and binomial logistic regression.ResultsThe weighted study sample included 2,608 participants. The mean STAY-S score of the total sample was 22.88 ± 12.25. In the total sample, 15.2% (n = 398) of participants were classified as having anxiety. The odds ratio (OR) of having anxiety was higher in females (OR = 2.44; 95% CI 1.75–3.33) and people who had experienced mental health problems in the past (OR = 1.45; 95% CI 1.03–2.04), had suicide attempt in the past (OR = 1.68; 95% CI 1.08–2.59), were worried about their health status due to COVID-19 (OR = 1.64; 95% CI 1.36–1.16), were worried about stigmatization from others if infected with COVID-19 (OR = 1.18; 95% CI 1.03–1.35), were worried about information regarding COVID-19 from the Internet (OR = 1.24; 95% CI 1.08–1.43), persons who were lonely (OR = 1.90; 95% CI 1.54–2.34), and persons with negative problem orientation (OR = 1.26; 95% CI 1.06–1.51). Protective factors were identified as having good self-rated general health (OR = 0.68, 95 % CI 0.58–0.81), maintaining a daily routine (OR = 0.74, 95 % CI 0.61–0.90), having financial stability (OR = 0.66, 95 % CI 0.55–0.79), and having good psychological resilience (OR = 0.90, 95 % CI 0.87–0.94).ConclusionsThis is the first study to report a prevalence of anxiety in the general population of Latvia. Certain factors that predict anxiety, as well as protective factors were identified.